Wind Walker - Edwards, Cassie (New York : Signet, 2004)
Yearning for adventure, Maggie Tolan convinces her mother to leave Boston-and everything they have ever known-for the wilderness of the frontier. But by the time she reaches the Wyoming territory, Maggie has lost her mother- and her desire to go on. Until she meets a Cheyenne Warrior who takes her breath away...
Keywords: Romance